Christian Tradition and Education for Human Rights: Criticism to Nietzsche's Moral Sense - Mujica Johnson, Felipe Nicolás (2020)
The philosophy of human rights contains the contribution of different traditions of thought that have contributed to the moral progress of humanity. And among them is the Christian tradition, which contributed to the concept of person and its inherent universal dignity. However, there are thinkers who deny the moral potential of this perspective, so this essay will address the thinking of one of them. So, the objective of this essay is to contrast the axiological ideas of the philosopher Friedrich Nietzsche with the essence of Christian morality and its contribution to human rights education. Thus, it is discovered that it is not true that the Christian moral sense is aimed at weakening or making people sick, but that it is oriented towards their moral strengthening. Precisely, this is done in order for them to overcome the vital or physiological limitations that make it difficult to sacrifice subjective well-being for an objective well-being at the individual and collective levels. Otherwise, if nature is not transcended, it is not possible to aspire to spiritual ends, such as universal fraternity. Consequently, it is recognized that it is fundamental to foster an inalienable philosophical attitude towards human rights in pedagogical contexts.